أثر مؤشرات التركيب الديمغرافي للسكان في الإنفاق الاستهلاكي للأسرة في سورية - الرفاعي, عبد الهادي; دخول, نبال (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study aimed at reducing the number of demographic structure indicators and utilizing from the main components resulting from conducting Factor Analysis in building a mathematical model that represents the relationship between the main components which represent demographic structure indicators and households' spending in Syria. The most prominent results were: by using Factor Analysis, three main components appeared to best represent demographic structure indicators. The first component includes: the percentage of urban population to total population, workforce distribution, divorce certificates. The second component is the percentage of males to total population. The third component is the percentage of total aid. A mathematical model is developed which links the three components of demographic structure indicators and the total monthly households' spending in Syria using multiple linear regression. هدف هذه الدراسة هو تخفيض عدد مؤشرات التركيب الديمغرافي والاستفادة من المركبات الأساسية الناتجة من تطبيق أسلوب التحليل العاملي في بناء النموذج الرياضي الذي يمثل العلاقة بين المركبات الأساسية الممثلة لمؤشرات التركيب الديمغرافي والإنفاق الاستهلاكي للأسرة في سورية. وكانت أهم النتائج: أنه تم التوصل إلى ثلاثة مركبات أساسية باستخدام أسلوب التحليل العاملي تمثل مؤشرات التركيب الديمغرافي أفضل تمثيل وهي: المركب الأول يضم (نسبة السكان الحضر من مجموع السكان، توزع المشتغلين، شهادات الطلاق)، المركب الثاني هو نسبة الذكور من مجموع السكان، المركب الثالث هو نسبة الإعالة الكلية، وتم التوصل إلى نموذج رياضي يربط بين المركبات الثلاث لمؤشرات التركيب الديمغرافي والإنفاق الشهري الكلي للأسرة في سورية باستخدام الانحدار الخطي المتعدد.